Fractography as a tool to assess the occurrence of fatigue fractures in complex microstructure structural components - D. Firrao; P. Matteis (Fracture and Structural Integrity)
Fractographic assessment of fatigue fractures may be difficult if they occur in metallic components characterized by low ductility complex microstructures. In these cases reconciliation of known fatigue rupture mechanisms with fractographic appearance of fatigue fractured surfaces is challenging. Special techniques coupled with theory development may be necessary. Pearlitic steels or steels with predominant pearliticmicrostructures are among the ones that are visited and their fatigue fractures interpreted. Analogously, fatigued Al foundry alloys, with hypoeutectic Al-Si compositions, are also illustrated.